Heterogeneity of Mouse Macrophages in Terms of Their Bactericidal Activity - Musa, M; Rowley, D. (1990)
These studies confirm that not all cells in a macrophage population express efective bactericidal functions. Two subsets of macrophages with cell-surface markers recognized by two monoclonal antibodies, designated M43 and 1\157 were shown to be involved in the bacteicidal activity of a macrophage population. B)' indirect radio immunoassay (RIA), it was found that these two subset markers were expressed more on the 5tu/ace of activated manipulates than on normal cells. It seems possible that these two markers may se11Je as markers for macrophage activation in terms of enhanced bactericidal activity.